2011
DOI: 10.1002/pon.1772
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of masculinity and self‐image in adolescent and young adult testicular cancer survivors: implications for romantic and sexual relationships

Abstract: Objective To examine adolescent and young adult (AYA) testicular cancer survivors’ subjective understanding of the impact of cancer in adolescence and young adulthood, with a particular emphasis on romantic and sexual relationships. Methods Twenty-one AYA testicular cancer survivors, aged 18 to 34 years, were recruited from outpatient testicular cancer follow-up clinics and completed a semi-structured qualitative interview that assessed the impact of testicular cancer on their romantic and sexual relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 35 publications
4
89
0
Order By: Relevance
“…Masculinity and self-image were impacted among testicular cancer survivors, who perceived the following social challenges: feeling different, viewing their differences as “damaged goods,” struggles with cancer-related disclosures, and feelings of embarrassment that directly lead to treatment and medical care delays [12]. …”
Section: Resultsmentioning
confidence: 99%
“…Masculinity and self-image were impacted among testicular cancer survivors, who perceived the following social challenges: feeling different, viewing their differences as “damaged goods,” struggles with cancer-related disclosures, and feelings of embarrassment that directly lead to treatment and medical care delays [12]. …”
Section: Resultsmentioning
confidence: 99%
“…As discussed, this topic has received relatively little attention in previous research [1]. A limited number of studies have previously examined the impact of visible difference/altered appearance on the formation of romantic and intimate relationships, but whilst these have included people with a range of visible differences [23], skin conditions [39,40], cancer [41] and burns scarring [42], the experiences of people with amputations have received comparatively and surprisingly little attention. Recent research [43] has identified support from romantic partners to be one of the factors that can influence adjustment to an unusual appearance or visible difference.…”
Section: Discussionmentioning
confidence: 99%
“…This has been suggested in other studies as well. 16,18,19 Eiser and Kuperberg 20 confirm that changes in appearance and body image can have more impact than confronting the potential life-limiting nature of cancer.…”
Section: The Aya-director Rolementioning
confidence: 93%